When Halal and Haram meet the Haram prevails?: an analysis of the maxim and its application in contemporary issues - Omar, Muhammad Naim; Mahamad, Arifin; Mohd Napiah, Mohammad Deen; Abdullah, Mohamad Asmadi (AJBAS journal, 2012)
The question of Halal and Haramis most pertinent element to determine the legitimacy of an act. All act of man must be in accordance with what has been prescribed by the Lawgiver. Men are responsible for what they do in this world. Therefore all Muslims are obliged to ensure that their action must be in line with the teaching of the Shari‘ah. With reference to this, in cases where the ruling is clear about the lawful and unlawful of certain items and practices the problem does not arise. However, issues in which there is a mixture of lawful and unlawful elements, careful consideration must be taken before issuing any legal verdict. Among the guidelines followed is the maxim “When Halal and Haram meet the Haram prevails”. The article intends to investigate the extent to which this maxim is applicable.